The sales of cigarettes to minors in Brazil, Uruguay, and Argentina - Radecki, Thomas E. (Revista Brasileira de Cancerologia, 2023)
Objective: To stablish the readiness of merchants to sell cigarettes to minors in three Latin American countries. Design: A sample of SO establishments each were tested in six Brazilian cities, as well as Montevideo, Uruguay and Buenos Aires, Argentina. Minors 13 to 15-years-old attempted to purchase cigarettes at each store. In addition, two hundred Brazilian adults were surveyed about whether the law prohibiting tobacco sales to minors should be enforced. Main outcome measures: Cigarette sales to minors. Results: Three hundred ninety-nine out of four hundred establishments sold cigarettes to the children. Only one merchant in Curitiba, Brazil refused to sell to a minor. Ninety-three percent of Brazilian adults thought their tobacco age law should be enforced. Conclusion: The laws against selling cigarettes to minors in Brazil and Uruguay are totally disrespected and unenforced. Argentina lacks such a law due to a 1992 presidential veto. An inexpensive ihstectionsystem could markedly decrease sales to minors and significantly decrease tobacco usage by minors. The health benefits of such enforcement would be very high.